Mandapa with a large circular ceiling - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Undeshwar Temple has a large circular ceiling, while the toranas (ornamental gateways/arches) atop the central four pillars support an additional smaller concentric cusped arch circular ceiling. This intricately adorned ceiling portrays flying gods and goddesses holding their distinctive attributes.